Ideal Duration of Pretreatment Using a Gelatin Hydrogel Nonwoven Fabric Prior to Subcutaneous Islet Transplantation - Saito, Ryusuke; Inagaki, Akiko; Nakamura, Yasuhiro; Imura, Takehiro; Kanai, Norifumi; Mitsugashira, Hiroaki; Endo, Yukiko; Katano, Takumi; Suzuki, Shoki; Tokodai, Kazuaki; Kamei, Takashi; Unno, Michiaki; et al. (Cell transplantation, 2023)
Subcutaneous islet transplantation is a promising treatment for severe diabetes; however, poor engraftment hinders its prevalence. We previously revealed that a gelatin hydrogel nonwoven fabric (GHNF) markedly improved subcutaneous islet engraftment in comparison with intraportal islet transplantation. We herein investigated whether the duration of pretreatment using GHNF affected the outcome of subcutaneous islet transplantation. A silicone spacer with GHNF was implanted into the subcutaneous space of healthy mice at 2, 4, 6, or 8 weeks before transplantation, and then diabetes was induced 7 days before transplantation. Syngeneic islets were transplanted into the pretreated space. Blood glucose, intraperitoneal glucose tolerance, immunohistochemistry, inflammatory mediators, and gene expression were evaluated. The 6-week group showed significantly better blood glucose changes than the other groups (P < 0.05). The cure rate of the 6-week group (60.0%) was the highest among the groups (2-week = 0%, 4-week = 50.0%, 8-week = 15.4%). The number of von Willebrand factor (vWF)–positive vessels in the 6-week group was significantly higher than in the other groups at pre-islet and post-islet transplantation (P < 0.01 [vs 2-and 4-week groups] and P < 0.05 [vs all other groups], respectively). Notably, this beneficial effect was also observed when GHNF was implanted into diabetic mice injected with streptozotocin 7 days before GHNF implantation. The positive rates for laminin, collagen III, and collagen IV increased as the duration of pretreatment became longer and were significantly higher in the 8-week group (P < 0.01). Inflammatory mediators, including interleukin (IL)-1b, granulocyte colony-stimulating factor (G-CSF), and interferon (IFN)-γ, were gradually downregulated according to the duration of GHNF pretreatment and re-elevated in the 8-week group. Taken together, the duration of GHNF pretreatment apparently had an impact on the outcomes of subcutaneous islet transplantation, and 6 weeks appeared to be the ideal duration. Islet graft revascularization, extracellular matrix compensation of the islet capsule, and the inflammatory status at the subcutaneous space would be crucial factors for successful subcutaneous islet transplantation.